INFLUENCE COMBINATION OF WARM WATER COMPRESS AND FINGER HAND RELAXATION TO REDUCE HEADACHE IN HYPERTENSION PATIENTS - Dwinta Widya Navita; Putu Sintya Arlinda Arsa; Erwanto, Erwanto; Siti Kholifah (Universitas Airlangga, 2024)
Background: Hypertension is one of the main causes of premature death. Globally, sufferers reach one of the symptoms of headache. Warm water compresses and finger grip relaxation are commonly used as non-pharmacological therapy for these patients. This study aims to determine the effect of a combination of warm water compresses and finger grip relaxation to reduce headaches in hypertension sufferers. Methods: The research design used quasi-experiment non-equivalent control group. This study has collected data from June – July 2023 at Prima Husada Hospital, Malang. A sample of 42 people was determined through snowball sampling and divided into two groups of equal size (the experimental group with a combination treatment of warm water compresses and finger grip relaxation and the control group with only warm water compresses treatment). The research instrument was a Numeric Rating Scale (NRS) observation sheet. Then the data were analyzed using paired sample T test and independent sample T test. Results: The average pretest headache scale for the experimental group dominated by women aged 35-45 years who worked as IRT = 4.4762 (medium) and the control group dominated by women aged 46-55 years who worked as farmers = 4.7143 (medium); the average posttest headache scale for the experimental group = 2.7143 (mild) and the control group = 3.4286 (mild); and both treatments, both the combination of warm water compresses and finger grip relaxation and warm water compresses alone, have a significant effect in reducing headaches for hypertension sufferers (each pvalue = 0.000), but the effects of the two are not significantly different. (p-value = 0.078). Conclusion: These two treatment models are useful in reducing hypertension headaches, although the effectiveness of their effects is not significantly different. Therefore, health service institutions such as hospitals can choose one of the two to be used as a complementary therapy for headaches for hypertension sufferers.